The Impact of Advancing Women's Rights on Nutritional Stability in a Politically Driven Economy - Ebun, Balogun Blessing (Kashere Journal of Politics and International Relations, 2025)
This paper explores the complex relationship between Advancing Women's Rights on nutritional stability, particularly in politicized economies. It examines the complex relationship between women’s empowerment and food security, highlighting how political dynamics influence this relationship. In contexts where political dynamics heavily influence resource allocation, governance, and social policy, the advancement of women’s rights plays a significant role in shaping food systems and household well-being. However, political instability or politicized decision-making often hampers progress. Through an analysis of gender-focused policies, agricultural systems, and socio-political structures, this study examines how women's rights contribute to improving nutritional outcomes and mitigating food insecurity in politically driven economies. The paper analyzes case studies from various regions to highlight the multifaceted relationship between women empowerment, food security, and political factors. Women empowerment, characterized by increased access to education, economic opportunities, and political participation, is hypothesized to play a critical role in enhancing food security. By leveraging case studies from various politicized economies, the study analyzes the correlation between women's empowerment and improvements in food availability, access, utilization, and stability. The findings suggest that empowering women leads to more efficient resource allocation, improved agricultural productivity, and better nutritional outcomes for households. Furthermore, the research highlights the challenges posed by political dynamics, such as policy instability and governance issues, which can hinder the progress of women empowerment initiatives. The paper concludes with policy recommendations aimed at integrating gender-focused strategies into food security programs to foster sustainable development in politicized economies.